Influence of the Presence of Poly(butylene succinate) in the Poly(ethylene terephthalate) Recycling Process - Cristina Pavon; Miguel Aldas; David Bertomeu; Harrison de la Rosa-Ramírez; María Dolores Samper; Juan López-Martínez (Clean Technologies, 2023)
Poly(butylene succinate) (PBS) is one of the contaminants in the Poly(ethylene terephthalate) (PET) recycling process. It is known that high contents of PBS in PET significantly reduce PET properties, but the effect of low contents on PET has yet to be studied. This work studied the influence of low contents of PBS on recycled PET. Five formulations of PBS in PET were prepared, and the properties of relative affinity, mechanical, thermal, and disintegration under composting conditions were assessed. The solubility parameter indicated that PET and PBS are miscible. However, FESEM images show slight marks of immiscibility, and the mechanical characterization results showed that PBS, even in low contents, reduced the mechanical properties of recycled PET, which proves that the materials are not miscible in the studied contents. The DSC results indicated that PBS could not be quickly detected in PET. However, its presence can be inferred by the reduction in PET crystallization degree. Finally, the presence of PBS up to 15 wt.% does neither affect the disintegration under composting conditions nor the thermal stability of recycled PET. The drop in mechanical properties shows that PBS must be removed from the PET waste stream to preserve the quality of the material.